EFFECTIVENESS OF THE SIPEKAT APPLICATION IN THE PERSONNEL OFFICE (BKD) OF SIDOARJO REGENCY - Aviana, Rizqillah Dita; Choiriyah , Ilmi Usrotin (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to evaluate the effectiveness of the SIPEKAT application in improving the promotion procedures for civil servants (ASN) in Sidoarjo Regency and to identify its impacts and challenges. Method: Employing a qualitative case study approach, the research collected data through interviews, observations, and document analysis involving users from the Development and Facilities Division of the Regional Civil Service Agency (BKD). Results: The findings reveal that SIPEKAT significantly reduces the time needed for processing promotion requests, enhances transparency and accountability in personnel management, and underscores the importance of human resource training and development to sustain innovation. However, technical issues such as limited facilities and varying staff competencies remain notable barriers. Novelty: This study contributes to the field by providing a comprehensive assessment of e-Government implementation within regional personnel systems and by offering innovative strategies to overcome technical and human resource-related challenges, thereby advancing the efficiency and effectiveness of local civil service administration.